Lesion Diameter Versus Inflammatory Biomarkers and Clinical Severity in Predicting Treatment Selection in Idiopathic Granulomatous Mastitis - Muhammet Fatih Keyif; Sabahattin Destek (World Journal of Surgery, 2026)
ABSTRACT Background Idiopathic granulomatous mastitis (IGM) is a rare chronic inflammatory breast disease with no established predictor to guide medical versus surgical treatment. Neutrophil‐to‐lymphocyte ratio (NLR) and C‐reactive protein (CRP) have been proposed, but prior reports rarely adjusted for lesion morphology or other markers of disease severity. We evaluated whether NLR, CRP, lesion diameter and clinical severity variables independently predict treatment selection in IGM. Methods Single‐center retrospective cohort of 71 women with biopsy‐proven IGM (2015–2019). An age‐matched control group ( n = 42) was selected from 74 healthy women. Pretreatment leukocyte, NLR, CRP and ultrasonographic lesion diameter were analyzed together with clinical severity variables (fistula/ulcer, multi‐quadrant involvement and axillary lymphadenopathy). Primary outcome was treatment modality (any surgery vs. medical only). Univariable and multivariable logistic regression were performed with an a priori biomarker‐focused model and an extended model incorporating severity variables. Sensitivity analyses assessed drainage‐only and excisional‐only subgroups. ROC analysis used bootstrap confidence intervals with pairwise DeLong tests. Results Surgical treatment was performed in 38 patients (53.5%; 30 drainage, 8 excisional); 33 (46.5%) received medical treatment only. After age matching, leukocyte, NLR and CRP were higher in patients than controls (all p < 0.001; large effect sizes). On univariable analysis, only lesion diameter predicted surgical treatment (OR 1.21 per mm; p < 0.001). In the biomarker‐focused multivariable model, only lesion diameter remained independent (aOR 1.23; 95% CI 1.11–1.36; p < 0.001). In the extended model, lesion diameter retained independence (aOR 1.25; 95% CI 1.13–1.40; p < 0.001), whereas severity variables and biomarkers did not contribute; axillary lymphadenopathy showed an inverse association (aOR 0.08; p = 0.046), likely reflecting confounding with lesion size. Sensitivity analyses confirmed the predictive value of lesion diameter. Lesion diameter discriminated treatment selection with high accuracy (AUC 0.914; 22 mm cut‐off: sensitivity 92.1%, specificity 84.8%); the extended model did not improve on this (AUC 0.918; ΔAUC +0.004; DeLong p = 0.89). Conclusion Inflammatory biomarkers and standard severity variables did not add independent predictive value beyond ultrasonographic lesion diameter for the medical‐versus‐surgical decision in IGM. NLR and CRP nonetheless correlated with lesion burden and may retain a role as markers of inflammatory activity rather than as independent selectors of treatment. These findings should be interpreted as predictors of treatment selection under the studied decision‐making pattern rather than as intrinsic markers of disease severity.